Life History Parameters of Diachasmimorpha longicaudata on Ceratitis capitata Under Laboratory Conditions: Implications for Mass Rearing and Biological Control - Harbi, Ahlem; Abbes, Khaled; Chermiti, Brahim; Martins, David S.; Hafsi, Abir; Sabater-Munoz, Beatriz; Beitia, Francisco J. (Institution of the Agricultural Research and Higher Education (IRESA), 2021)
The Mediterranean fruit fly, Ceratitis capitata, is considered one of the most destructive pests worldwide. The braconid Diachasmimorpha longicaudata is the most widely used parasitoid in biological control programs of tephritids. It has been mass-reared and used in augmentative releases against major fruit fly species in tropical and subtropical countries, and recently in the Mediterranean Basin. After its introduction into Spain and then Tunisia, reproductive and demographic parameters have been studied on C. capitata under laboratory conditions. These parameters were compared to those published elsewhere. The role of artificial diet for rearing the host is discussed. Our findings showed the good fitness of the parasitoids produced on C. capitata in laboratory with a generation time of 28.1 days, a reproductive rate of 39.2, an intrinsic rate of increase of 0.125, a doubling time of 5.2 days and the finite rate of increase (per day) was 1. Involvements on the biological control of the Mediterranean fruit fly in Tunisia are discussed.